Myxidium finnmarchicum n. sp. (Myxosporea: Myxidiidae) from the gall bladder of whiting Merlangius merlangus (L.) (Pisces: Teleostei) in North Norway - Mackenzie, Ken; Collins, Catherine; Kalavati, Chaganti; Hemmingsen, Willy (Zootaxa, 2010)
A new species of myxosporean is described from the gall bladder of whiting Merlangius merlangus (L.) (Pisces: Teleostei) caught at the northernmost extremity of the range of this fish off the northwest coast of Finnmark county, North Norway. The new species, Myxidium finnmarchicum, is described morphologically and genetically and compared with other similar species of Myxidium reported from the gall bladders of gadid fish in the North Atlantic - M. sphaericum, M. gadi and M. bergense. Both the morphological and molecular descriptions support the status of Myxidium finnmarchicum as a new species. Myxidium sphaericum is a parasite of whiting in the North Sea, but the two species are separated geographically by an intervening area in the northern North Sea north of 58° N where no whiting has been found infected with any species of Myxidium. Based upon 18S rRNA analysis, M. finnmarchicum shows closest sequence identity to M. gadi. The confusion in the literature regarding the validity and host specificities of M. sphaericum, M. gadi, M. bergense and M. incurvatum is highlighted and discussed. We suggest that a more detailed investigation of the range of morphological and molecular variation in these parasites from their various reported host species is required.